PENGARUH PROFITABILITAS TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Rizky Halimah; Esti Damayanti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This research was conducted on manufacturing companies in the basic and chemical industry sectors on the Indonesia Stock Exchange for the 2017-2020 period.The type of research used is quantitative research and uses purposive sampling. The number of samples of this study was 24 companies during the 4-year research period, so that a sample of 96 data was obtained, but the final sample was obtained as many as 91 data. The results of the prove that profitability has an effect on audit delay and company size is not able to moderate the relationship between profitability and audit delay in basic and chemical industrial companies on the Indonesia Stock Exchange for the 2017-2020 period.